MOBILE LEARNING AMONG FORM SIX STUDENTS: ARE THEY READY? - Jol Kankok; Abdul Said Ambotang; Syahrul Nizam Salam, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Prior to embarking on mobile technologies, mobile learning has become an integral part of learning strategies. It is viewed as a potentially significant learning tool as it has made learning ubiquitous with the use of wireless mobile devices. However, before designing and implementing a new learning system, learner’s readiness should be taken into consideration. Despite its notable advantages, mobile learning is largely unresearched at Malaysian Form Six Students. Therefore, this quantitative study aims to investigate the extent of readiness of Malaysian Form Six students., A set of questionnaires was administered to 106 randomly selected form six students to serve this purpose. The questionnaire was designed to explore three main readiness, namely Self-Directed Learning (SDL), technological readiness, and psychological readiness. The overall findings revealed that a great majority of the students show a high level off readiness for the implementation of mobile learning. The evidence from this preliminary finding has provided valuable information for educators and curriculum designers to discover ways to exploit mobile learning in the teaching and learning process.